Dolutegravir, abacavir and lamivudine as HIV therapy. (May 2014) - Fernandez-Montero, Jose Vicente; Barreiro, Pablo; Labarga, Pablo; De Mendoza, Carmen; Soriano, Vicente
<x xml:space="preserve">Abstract</x> Introduction: Antiretroviral therapy has evolved dramatically and more potent, safer and convenient drugs have replaced former compounds. Dolutegravir (DTG) is the most recently approved integrase inhibitor. It displays attractive properties such as one pill once daily (QD) dosing, high barrier to resistance and clean safety profile. Moreover, it is planned to be marketed, co-formulated with abacavir (ABC) and lamivudine (3TC) as a single-tablet regimen (STR). The availability of this QD single pill represents a significant step further for a large number of HIV-infected persons. Areas covered: Updated summary of evidence-based information on efficacy and safety of DTG along with ABC and 3TC. All information available on antiretrovirals in the most advanced stages of clinical development reported in peer-reviewed journals or at international meetings has been reviewed. Expert opinion: The combination of <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=DTG, ABC and 3TC&logicalOpe1=OR&field2=articletitle&text2=DTG, ABC and 3TC&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">DTG, ABC and 3TC displays a high efficacy, superior to many other antiretroviral combinations, including other convenient STR. The good safety profile, low potential for drug interactions and high resistance barrier of DTG- ABC-3TC are unique features than make this co-formulation the preferred choice as HIV therapy in multiple clinical scenarios, including most treatment-naïve and treatment-experienced patients, as part of switch strategies, and in patients with underlying serious medical conditions such as kidney abnormalities, liver disease, metabolic disturbances or neuropsychiatric conditions.